“These Are the Things You Are to Do”: A Newly Discovered Fragment of the Book of Zechariah from the Greek Minor Prophets Scroll (8ḤevXIIgr) - Riestra, Beatriz (Textus, 2022)
This paper aims to provide a preliminary edition of a new fragment of the Greek Minor Prophets scroll (8ḤevXIIgr; Rahlfs’ siglum 943) containing Zech 8:16–17. The fragment was discovered in an excavation conducted by the Israel Antiquities Authority in the Cave of Horror (Naḥal Ḥever) at the end of 2019. Provided that for certain passages 8ḤevXIIgr is the only textual witness preserved in the Judean Desert and given the fact that it predates the earliest Greek manuscript previously known by at least three centuries, every new fragment can potentially add fresh information, raise new questions, and ultimately join an additional piece to the puzzle of our understanding of the biblical text and its transmission.